Element composition of insoluble fraction of aerosols in snow in the vicinity of oil chemistry refinery (Pavlodar city, Kazakhstan) and petrochemical plant (Tomsk city, Russia); Proceedings of SPIE; Vol. 9680 : Atmospheric and Ocean Optics: Atmospheric Physics - Talovskaya A. V. Anna Valerievna; Filimonenko E. A. Ekaterina Anatolievna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Shakhova T. Tatiana; Parygina I. A. Irina Alekseevna (Optical Radiation Propagation In The Atmosphere And Ocean, 2015)
Title screen